Analisis Sistematis Peran Etika Bisnis dan Corporate Social Responsibility dalam Sektor Keuangan - Arista Supardi; Fatma Dilla Rahayu; Bunga Asri Helennia; Asshira Anjani (Indonesia Economic Journal, 2026)
This study aims to systematically analyze the role of business ethics and Corporate Social Responsibility (CSR) in strengthening integrity and sustainability within the financial sector. This research employs a Systematic Literature Review (SLR) method on journal articles relevant to business ethics, CSR, corporate governance, and financial performance in banking and financial institutions. The synthesis results indicate that the implementation of CSR and business ethics practices positively influences financial performance, corporate reputation, and firm value. Transparent CSR disclosure has been proven to enhance investor trust and customer loyalty, particularly in industries that rely heavily on trust. Furthermore, Good Corporate Governance (GCG) mechanisms such as independent boards of commissioners and audit committees strengthen the effectiveness of CSR implementation and minimize conflicts of interest. In Islamic banking institutions such as Bank Syariah Indonesia Tbk, CSR also reflects the implementation of Islamic ethical values emphasizing trustworthiness and social responsibility. Overall, the integration of business ethics, CSR, and corporate governance serves as a crucial pillar in building a transparent, accountable, and sustainable financial sector.